The Implementation of Word Games to Improve Students’ English Vocabulary Proficiency - Khusaini, Fakhri; Fauziah, Nurul (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
This research aims to identify the influence of using word games on students' proficiency of English vocabulary. The method used was an experiment with a quasi-experimental approach, involving two groups of students in the 6th semester of the Primary School Teacher Education Study Program at STKIP TAMAN SISWA BIMA. A total of 40 students were randomly selected and divided into two groups: an experimental group that used word games and a control group that used conventional learning methods. The research instrument is a vocabulary proficiency test (pre-test and post-test). The results showed that the average post-test score of the experimental group increased significantly compared to the control group. The average increase in score in the experimental group was 12.7 points, while in the control group it was 8.75 points. Statistical analysis using the paired sample t-test shows a significant value. (two-tailed) = 0.000, which means there is a significant difference between the two groups with a confidence level of 95%. Based on these results, it is recommended that educational institutions consider integrating word games into the English language learning curriculum to increase the effectiveness of vocabulary learning. This research makes an important contribution to the field of language education by showing that word games can be an effective and enjoyable learning method.